Phosphorescence of vitreous 2-bromobenzophenone - Buravtseva, L.M.; Pyshkin, O.S.; Strzhemechny, M.A.; Avdeenko, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Spectroscopic studies of vitreous 2-bromobenzophenone have been carried out over the respective domain of its stability. Glassy 2-bromobenzophenone samples were obtained by abrupt cooling of the melt by cold helium vapor. Quantum yield measurements allowed us to establish that the upper boundary of stable glass is slightly above 100 K while at about 220 K the glass melts. Phosphorescence measurements at 4.2 K showed that even at this low temperature the emission contains a strong excimer component. The energy position and shape (two bands) of the excimer emission are close to those observed in the crystal of 2-bromobenzophenone at higher temperatures. Contrary to findings in the crystal, the monomeric emission of the glass contains only one C=O stretch series, every band of which is substantially broader than in the crystal. As the temperature is raised, the monomeric emission intensity goes down to completely disappear above 70 K.